2012
DOI: 10.2131/jts.37.1253
|View full text |Cite
|
Sign up to set email alerts
|

Acute oral toxicity evaluation of symmetrically branched glycerol trimer in ddY mice

Abstract: -Lipophilic-hydrophilic balance is a quite important determinant of pharmacokinetic properties of pharmaceuticals. Thus it is a key step to successfully manage lipophilic-hydrophilic balance in drug design. We have designed unique modular molecules, symmetrically branched oligoglycerols (BGL) as an alternative means to endow hydrophobic molecules with much hydrophilicity. We have succeeded in improving the water-solubility of several hydrophobic medicinal small molecules and thermal stability of artificial pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 23 publications
3
9
0
Order By: Relevance
“…Even if BGL003 is cut out in the body, we have confirmed its biological safety by evaluating acute oral toxicity in mice and cytotoxicity, although our digestion study suggests that BGL003 was not expected to be produced by hepatic drug conversion (Figures 7 and 8). 12,15 We also have demonstrated striking facilitation of lipid-lowering effects and hydrophilicity of fenofibrate by conjugating to BGL003. 14 The study revealed that the BGL003-conjugated fenofibrate derivative is a prodrug and rapidly cleft, producing BGL003free fenofibric acid when administered to rodents, while SN38-BGL A did not yield free SN38.…”
Section: ■ Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Even if BGL003 is cut out in the body, we have confirmed its biological safety by evaluating acute oral toxicity in mice and cytotoxicity, although our digestion study suggests that BGL003 was not expected to be produced by hepatic drug conversion (Figures 7 and 8). 12,15 We also have demonstrated striking facilitation of lipid-lowering effects and hydrophilicity of fenofibrate by conjugating to BGL003. 14 The study revealed that the BGL003-conjugated fenofibrate derivative is a prodrug and rapidly cleft, producing BGL003free fenofibric acid when administered to rodents, while SN38-BGL A did not yield free SN38.…”
Section: ■ Discussionmentioning
confidence: 78%
“…However, CPT-11 still has low water solubility, and other hydrophilic derivatives of camptothecin like PEG-conjugated SN38 have been explored to minimize adverse effects and maximize the pharmacological merits. We have been developing another versatile strategy to endow hydrophobic molecules with much hydrophilicity by conjugating with branched glycerol oligomers. The water solubility of fenofibrate, one of the most hydrophobic agents in clinical use, was >2000-fold improved just by conjugating to branched glycerol trimer (BGL003) . Furthermore, the BGL003-conjugated fenofibrate exhibited >10-fold stronger lipid-lowering effects as well as ∼5-fold higher concentrations in blood in rodent models. , In addition, the biological safety of BGL003 has been confirmed in terms of acute oral toxicity and cytotoxicity. , Therefore, the conjugation with branched glycerol oligomers could be a prospective way to ameliorate camptothecin-derived compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many phytochemicals, especially, polyphenols are too hydrophobic to be absorbed into the body enoughly. We have been developing a novel technology for improving water-solubility of the hydrophobic molecules by conjugating it with branched glycerol oligomers (BGLs) (11,(54)(55)(56)(57). Pharmacological, pharmacokinetic, and physical properties of such highly hydrophobic compound as fenofibrate were strikingly ameliorated when conjugated with the BGL trimer without any adverse effects.…”
Section: Can We Obtain Exercise-related Benefits Just By Eating Foods?mentioning
confidence: 99%
“…5−15 In addition, we have demonstrated biological safety of BGL003, the simplest BGL in cultured cells and rodents, suggesting BGL is innoxiously applicable to a prodrug. 15,16 However, it remained unclear whether the molecular modification by conjugation to BGL actually improves ADME properties of pharmaceuticals in terms of pharmacological effects.…”
Section: ■ Introductionmentioning
confidence: 99%